The neuroimmune response to cryptococcal infection - Kauchali, Maahir (Department of Human Biology, 2024)
Cryptococcal meningitis (CM) is a fatal fungal infection of the brain that is responsible for up to 20% of all AIDS-related deaths globally, 75% of which are from Sub-Saharan Africa. CM is characterised by debilitating neurological damage often resulting in death or serious longterm sequelae even after receiving treatment. Despite the brain being the main organ of injury, there is a paucity of data describing the interaction of the fungus with resident immune cells of the brain. The aim of this study was to investigate the neuroimmune response to cryptococcal infection using a novel organotypic brain slice culture system. We treated cultured brain slices with either whole cell C. neoformans, its purified capsule (a known major virulent factor) or lipopolysaccharide (LPS), and compared them to untreated control slices. The neuroimmune response was measured by tracking the activation of nuclear factor for interleukin 6 (NF-IL6), and confirmed by measuring the release of IL6 and tumour necrosis factor- (TNF-α). Our results showed that neither C. neoformans nor its purified capsule elicited a neuroinflammatory response as observed in LPS-treated slices. Co-stimulation of LPS-treated slices with C. neoformans or its purified capsule did not abolish an LPS-induced inflammatory responses in brain slices. Our findings also show that microglia are the principal cells that phagocytose fungal cells during cryptococcal infection and that even after engulfing fungal cells, microglial cells were not classically activated. Therefore, we concluded that C. neoformans recognition by resident immune cells, on its own, may not be responsible for the debilitating inflammatory response observed during CM, and that the purified cryptococcal capsule does not elicit an inflammatory or anti-inflammatory response.